Seismic analysis of underground structures: Influence of soil type, relative stiffness and earthquake intensity - Garcia Velasquez, Jhonatan Smith (2022)
Underground structures serve as means of carrying out essential activities in a modern society; therefore, their proper seismic performance is important in the mitigation of the risk of disasters. This work addresses the seismic effects on underground structures in highly seismic areas such as the coast of Perú. The software FLAC was used to perform dynamic analyses of underground structures with rectangular section, using free-field type boundary conditions, accounting for the nonlinear inelastic behavior of the soil, under seven earthquakes matched to the same target spectrum. The analyses were carried out for different earthquake intensities, varying the soil characteristics (homogeneous or stratified) and the geometry of the structure. The results show that when the structure is placed in a homogeneous soil the forces and displacements have only small variations. However, when it is placed in a heterogeneous soil, the results show important differences. Thus, matching to the same target spectrum does not imply a uniform seismic demand. The geometry of the structure and the wall thickness have considerable influence. In heterogeneous soils a relatively flexible structure may experience large deformations and important damage.